Efektivitas Beberapa Jenis Ikan dalam Mengonsumsi Eceng Gondok (Eichhornia crassipes (Mart) Solms.) di Danau Tondano, Kabupaten Minahasa - Rama Presley Kambey; Rose Olivia Shirley Elisabeth Mantiri; Markus Talintukan Lasut (Jurnal Ilmu Pertanian Indonesia, 2019)
This research was conducted to determine the type of fish that effectively consumed water hyacinth in Tondano Lake. This research was conducted during August to December 2017. To know the effectivenes of fish that consume water hyacinth is using grasscarp, silverbarb, marble goby, and snakehead gudgeon fish with size range of 10-30 cm were used. Aquarium size of 120 x 40 x 40 cm was used as tank equipped with camera for observation. The results showed that grasscarp effectively consume 3.2 g of water hyacinth per day.